The literary expression of national trauma in Irish and Ukrainian literatures - Krol, Tatiana (Studia Rossica Posnaniensia, 2020)
The most tragic and traumatic experiences in the respective histories of Ireland and Ukraine were their Great Famines. This paper discusses literary techniques used for the expression of national trauma in Irish and Ukrainian famine fictions. It examines the representations of An Gorta Mór and the Holodomor in The Silent People by Walter Macken, The Hungry Land by Michael Mullen, Maria: A Chronicle of a Life by Ulas Samchuk and Sweet Snow by Alexander J. Motyl, and demonstrates that the rhetoric of a national character occupies a prominent position in the novels. Exploring images of the Self and the Other within the oppressor/oppressed dichotomy, expressed from the perspective of the latter, the paper argues that national character stereotypes function to highlight the detrimental effects of British rule in Ireland and Soviet rule in Ukraine. Imagology and trauma studies underpin the paper’s theoretical framework. The paper is part of the doctoral thesis An Imagological Study of the Depiction of the Irish and Ukrainian Great Famines in the novels by Samchuk, Macken, Motyl and Mullen, supervised by Dr. Brigitte Le Juez and Dr. Áine McGillicuddy, defended in December 2018 at Dublin City University.